Self-harm in older adults: systematic review. (21st February 2019) - Troya, M. Isabela; Babatunde, Opeyemi; Polidano, Kay; Bartlam, Bernadette; McCloskey, Erin; Dikomitis, Lisa; Chew-Graham, Carolyn A.
Abstract : Background: Self-harm is a major public health concern. Increasing ageing populations and high risk of suicide in later life highlight the importance of identification of the particular characteristics of self-harm in older adults. Aim: To systematically review characteristics of self-harm in older adults. Methods: A comprehensive search for primary studies on self-harm in older adults was conducted in e-databases (AgeLine, CINAHL, PsycINFO, MEDLINE, Web of Science) from their inception to February 2018. Using predefined criteria, articles were independently screened and assessed for methodological quality. Data were synthesised following a narrative approach. A patient advisory group advised on the design, conduct and interpretation of findings. Results: A total of 40 articles ( n = 62 755 older adults) were included. Yearly self-harm rates were 19 to 65 per 100 000 people. Self-poisoning was the most commonly reported method. Comorbid physical problems were common. Increased risk repetition was reported among older adults with self-harm history and previous and current psychiatric treatment. Loss of control, increased loneliness and perceived burdensome ageing were reported self-harm motivations. Conclusions: Self-harm in older adults has distinct characteristics that should be explored to improve management and care. Although risk of further self-harm and suicide is high in all age cohorts, risk of suicide is higher in older adults. Given the frequent contact with health services, an opportunity exists for detection and prevention of self-harm and suicide in this population. These results are limited to research in hospital-based settings and community-based studies are needed to fully understand self-harm among older adults. Declaration of interest: None.